Penjor Galungan Di Tengah Perubahan Sosial Di Desa Kapal, Mengwi Kabupaten Badung - Santika Dewi, Luh Ayu Ari; Kebayantini, Ni Luh Nyoman; Suka Arjawa, I Gusti Putu Bagus (JURNAL ILMIAH SOSIOLOGI: SOROT, 2019)
ABSTRACT Penjor is one of the religious facilities as offerings in every ceremony and also symbolizes Mount Agung. Penjor is commonly used at piodalan, welcoming the Galungan and Kuningan and the other ceremonies. Penjor was made for rituals, but modernization made penjor a commodity. The theory in this study is the theory of linear evolution (Herbert Spencer). Based on the results of this study it is known that penjor in the midst of social changes that occur in the village of the Ship is caused by limited time, and energy, economic limitations. Then the impact of penjor Galungan in the midst of social change has an impact on the economic, social, material and cultural fields. Penjor Galungan in the midst of social change provides solutions to people who have limited time, energy, and material can still do yadnya without reducing the meaning of the ceremony. Keywords: Penjor, Ceremony, Hindu-Bali, Social Changes